Temporal and Spatial Effects on the Diet of an Estuarine Piscivore, Longnose Gar (Lepisosteus osseus) - McGrath, Patrick E.; Hilton, Eric J.; Musick, John A. (Estuaries and coasts, 2013)
Chesapeake Bay is the largest estuary in the USA and comprises vast areas of polyhaline to freshwater, tidal fish habitat. The Bay experiences large temperature differences between winter and summer, which in combination with the variety of salinities enables approximately 240 species of fish to be temporary inhabitants. This dynamic environment leads to an ever-changing prey field for predators. The goal of this study was to characterize the diet of one of the few resident, euryhaline predators within the tidal rivers in Virginia, Lepisosteus osseus (longnose gar). The top five prey species were Morone americana, Brevoortia tyrannus, Fundulus spp., Micropogonias undulatus, and Leiostomous xanthurus. The diet composition varied with the seasonal fish assemblages, length of L. osseus, water temperature, and salinity. L. osseus consumed a greater amount of marine and anadromous fishes (%W=59.4 % and %N=56.5 %) than resident fishes (%W=40.6 % and %N=43.5 %). The seasonal influx of anadromous or coastal spawning fishes appears to be an important prey source for L. osseus and most likely other piscivores in the tributaries of Chesapeake Bay.